Bugs got milk? Exploring the potential of lactose as a prebiotic ingredient for the human gut microbiota of lactose-tolerant individuals - Pessotti, Rita de Cassia; Guerville, Mathilde; Agostinho, Laira Lorraine; Bogsan, Cristina Stewart Bittencourt; Salgaço, Mateus Kawata; Ligneul, Amandine; Freitas, Miller Nunes de; Guimarães, Cristiano Ruch Werneck; Sivieri, Katia [UNESP] (Elsevier, 2025)
Milk consumption is important to help meet daily nutrient requirements. However, lactose—present in dairy products—has been associated with digestive discomfort in individuals who are lactose intolerant or have inadequate lactase activity. Yet, a new perspective on this dietary component has emerged: its potential as a prebiotic for the lactose-tolerant population. We hypothesized that ingestion of lactose may improve the microbial community structure and metabolism of the gut microbiota from healthy adults. First, we assessed the acute impact of lactose ingestion on the gut microbiota of adults using a short-duration in vitro batch colonic model. Subsequently, we employed a long-duration in vitro dynamic multivessel colonic model to evaluate the effects of lactose chronic ingestion. In both cases, a mixture of lactose/galactose/glucose was administered in a defined proportion to mimic lactose metabolism and galactose/glucose absorption in lactose-tolerant adults. The hypothesis was confirmed, as a modulatory prebiotic effect was revealed on the microbial community structure and metabolism of the microbiota upon treatments simulating the ingestion of three doses of lactose, equivalent to half a glass, one glass, and two glasses of cow's milk. The long-duration model confirmed this potential, increasing the relative abundance of the beneficial genera Lactobacillus, Akkermansia, and Faecalibacterium, while the usually detrimental genus Clostridium decreased. Additionally, the health-promoting microbial metabolites acetate, propionate, and lactate were increased. Therefore, lactose ingestion could positively modulate the gut microbiota in healthy lactose-tolerant adults, thereby promoting gut health and shedding light on the dietary benefits of consuming milk.
Keywords: Gut microbiota; Lactose; Milk; Prebiotic effect; Short-chain fatty acids